Review of the Fund's Strategy on Anti-Money Laundering and Combating the Financing of Terrorism. (Policy Papers; Policy Paper, 2014)
The Fund's Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) program represents an important contribution to the international community's response to money laundering and terrorist financing over the past decade. The program originally focused primarily on (a) AML/CFT assessments - as part of the Reports on the Observance of Standards and Codes (ROSC) program and of the Financial Sector Assessment Program (FSAP) - and (b) capacity development activities. Following guidance provided by the Board in 2011, money laundering, terrorist financing and related predicate crimes issues (hereinafter also referred to as financial integrity issues) are being raised in the context of surveillance when they are judged to affect domestic and balance of payments stability. Moreover, some recent Fund-supported programs have also incorporated financial integrity issues.